Potential therapeutic targets for ischemic stroke in pre-clinical studies: Epigenetic-modifying enzymes DNMT/TET and HAT/HDAC - Guo, Yurou; Li, Jing; Liu, Xiaodan; Ding, Huang; Zhang, Wei (Frontiers in Pharmacology, 2025)
Ischemic stroke (IS) remains a leading cause of mortality and disability worldwide, driven by genetic predispositions and environmental interactions, with epigenetics playing a pivotal role in mediating these processes. Specific modifying enzymes that regulate epigenetic changes have emerged as promising targets for IS treatment. DNA methyltransferases (DNMTs), ten-eleven translocation (TET) dioxygenases, histone acetyltransferases (HATs), and histone deacetylases (HDACs) are central to epigenetic regulation. These enzymes maintain a dynamic balance between DNA methylation/demethylation and histone acetylation/deacetylation, which critically influences gene expression and neuronal survival in IS. This review is based on both in vivo and in vitro experimental studies, exploring the roles of DNMT/TET and HAT/HDAC in IS, evaluating their potential as therapeutic targets, and discussing the use of natural compounds as modulators of these enzymes to develop novel treatment strategies.